Male sex, Gustillo-Anderson type III open fracture and definitive external fixation are risk factors for a return to the or following the surgical management of geriatric low energy open ankle fractures. Issue 2 (February 2022) - Fourman, Mitchell S.; Adjei, Joshua; Wawrose, Richard; Moloney, Gele; Siska, Peter A.; Tarkin, Ivan S.
Highlights: Survival following an open ankle fracture in the geriatric (age > 60 years) population is more related to host characteristics than surgical management. Amputation or retrograde hindfoot nail should be considered over definitive external fixation in the setting of fractures with a severely compromised soft tissue envelope to reduce the risk of an unplanned return to the OR. However, these do not influence survival. Pre-operative mobility has a strong independent predictor of 90-day event (readmission or death) and 1-year mortality following an open ankle fracture in geriatric patients. Abstract: Introduction: Open ankle fractures in geriatric (age > 60 years) patients are a source of significant morbidity and mortality. Surgical management includes plate and screw fixation (ORIF), retrograde hindfoot nail (HFN), definitive external fixation (ex-fix) and below knee amputation. However, each modality poses unique challenges for this population. We sought to identify predictors of unplanned OR and short-term mortality after geriatric open ankle fractures managed by our service. Materials and methods: In an IRB-approved protocol, we evaluated patients over 60 years of age managed for a low energy open ankle/distal tibia pilon fracture by trauma fellowship-trained surgeons from a single academic department that covers two level I trauma centers. Our primary outcome was an unplanned return to the OR. Secondary outcomes were a 90-day "event", defined as an all-cause hospital readmission or mortality, and 1-year mortality. Differences with a p-value < 0.1 measured on univariate analysis were evaluated using a multivariable logistic regression to identify independent outcome predictors. Results: A total of 113 (60 ORIF, 36 HFN, 11 ex-fix, 6 amputations) were performed. Cohort mean age was 75.2 ± 9.8 years, and 31 patients (27.4%) were male. Mean age-adjusted charlson comorbidity index was 5.5 ± 2.0. Significant independent predictors of an unplanned return to the OR were male sex (OR 4.4, 95% CI 1.3 to 15.4), Gustilo Type III open fracture (OR 4.9, 95% CI 1.5 to 17.5) and ex-fix (OR 15.6, 95% CI 2.7 to 126.3). Independent predictors of a 90-day "event" were walker/minimal ambulation (OR 3.5, 95% CI 1.3 to 10.4), surgical site infection (OR 4.8, 95% CI 1.8 to 13.8) and reduced BMI (OR 0.9, 95% CI 0.9 – 0.99), while independent predictors of 1-year mortality were age (OR 1.1, 95% CI 1.003 to 1.2), ACCI (OR 1.4, 95% CI 1.02 to 2.0) and walker/minimal ambulator (OR 7.5, 95% CI 1.7 to 53) Conclusions: Host factors, particularly pre-operative mobility, were most predictive of 90-day event and 1-year mortality. Only definitive external fixation was found to influence patient morbidity as a significant predictor of unplanned OR. However, no surgical modality had any influence on short-term readmission or survival.